Eksplorasi Etnomatematika Pada Alat Musik Lenong Betawi Di Sanggar Sinar Fajar Depok - Humairoh, Humairoh; Nurrahmah, Arfatin (Himpunan: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2025)
This study aims to explore mathematical concepts embedded in the traditional musical instruments of Lenong Betawi at Sanggar Sinar Fajar in Depok. The research employs a qualitative descriptive method with an ethnographic approach. Data were collected through observation, in-depth interviews with cultural figures and artists, and visual documentation. The findings reveal that Lenong Betawi musical instruments contain mathematical elements such as plane geometry (squares, trapezoids, and circles), solid geometry (cylinders and hemispheres), as well as rhythmic patterns, symmetry, and proportional measurements related to sound frequency. These findings demonstrate a strong connection between culture and mathematics in everyday life, particularly within the Betawi local context. This study contributes to the development of contextual mathematics learning through ethnomathematical approaches and promotes cultural preservation through scientific inquiry. Therefore, traditional culture can serve as an effective medium for understanding mathematical concepts in a more meaningful and enjoyable way.